Firms’ Collaboration Within Their Business Networks in Bioenergy Technology: A Case Study - Lehtovaara, Matti; Kokkonen, Kirsi; Rousku, Petri; Kässi, Tuomo (International Journal of Industrial Engineering and Management, 2011)
Global warming is becoming a serious environmental concern, and current primary energy sources are also getting exhausted. Decentralized combined heat and power production using biofuels such as forest biomass could offer a qualified sustainable solution for many regions. The objective of this paper is to analyze what kind of heating plant manufacturers exist in the bioenergy field in Finland that also have future potential for supplying power generation units, and how they collaborate within their business networks. The primary sources of information for the industry evaluation were an analysis of major industry players based on financial and non-financial data and key expert interviews. The results reveal that the plant suppliers can be divided into three different clusters: network leaders, turnkey suppliers and distributors; and that they collaborate extensively within their business networks. The plant suppliers complement their own capabilities and competences by efficient networking that prepares the way for complete plant deliveries instead of component and parts supply only. Article history: Received (30.05.2011); Revised (30.05.2011); Accepted (19.09.2011)